Faire comme si et faire comme ça - Séverine Lagneaux (Swiss Journal of Sociocultural Anthropology, 2015)
Through four empirical imitation situations collected in the daily life of a dairy farm in Wallonia, this article examines the differences and similarities made between breeders, their cows and his milking robot. These imitative practices (cows mimicking them, farmer imitating his cattle, the robot mimicking the human and the breeder imitating the robot) question the classical, philosophical or psychological theories of imitation. I will also show that these relationships refer to analogism as defined by Philippe Descola.